Tabernaemontana crispa Roxb. (Apocynaceae) - A new angiospermic record for Bangladesh - Khanam, Mahbuba; Rahman, M Oliur; Uddin, Sarder Nasir (Bangladesh Journal of Plant Taxonomy, 2003)
No abstract available. Bangladesh J. Plant Taxon. 10(2): 73-76, 2003 (December)